Research on water resource carrying capacity of capital water conservation functional zone - Qin, Jing; Niu, Jie; Niu, Wenlong (Frontiers in Environmental Science, 2023)
Water resources are important for supporting regional economic development. A scientific and reasonable evaluation of the carrying capacity of water resources is of high significance to regional sustainable development. Zhangjiakou City is China's first capital water conservation functional area, which plays a role in ensuring the safety of water resources and ecological environment in the capital. Considering Chicheng County, Zhangjiakou City, as a typical area, its water resource carrying capacity in the current year (2018) and the plan year (2025) is evaluated by constructing a water resource carrying capacity evaluation index system for the county, determining the threshold of the bearing capacity evaluation index, and using the single-factor evaluation method and cloud theory method. In addition, the main factors affecting the water resource carrying capacity of Chicheng County are analyzed. The results show that the carrying capacity of water resources in the county in the current year is critical, and that the bearing capacity of the total water consumption elements in the plan year is not overloaded. Furthermore, the water resource carrying capacity of the current year and plan year belong to the third level of the evaluation index system. There is further scope for the carrying capacity of water resources in Chicheng County to satisfy its economic and social development. However, it is urgent to solve the problems affecting the water quality elements of rivers, such as heavy river water pollution, low sewage treatment capacity, and weak pollution monitoring and supervision. It is necessary to optimize the industrial economic structure of Chicheng County, accelerate the improvement of water resources management system and mechanism, and ensure the long-term safety of water resources and ecological environment in the capital.